System Center Configuration Manager Current Branch unleashed - Meyler, Kerrie; Holt, Byron; Jones, Garth (Computer scientist) (Unleashed., 2018)
System Center Configuration Manager Current Branch provides a total systems management solution for a people-centric world. It can deploy applications to individuals using virtually any device or platform, centralizing and automating management across on-premise, service provider, and Microsoft Azure environments. In System Center Configuration Manager Current Branch Unleashed, a team of world-renowned System Center experts shows you how to make the most of this powerful toolset. The authors begin by introducing modern systems management and offering practical strategies for coherently managing today's IT infrastructures. Drawing on their immense consulting experience, they offer expert guidance for ConfigMgr planning, architecture, and implementation. You'll walk through efficiently performing a wide spectrum of ConfigMgr operations, from managing clients, updates, and compliance to reporting. Finally, you'll find current best practices for administering ConfigMgr, from security to backups. Detailed information on how to: Successfully manage distributed, people-centric, cloud-focused IT environments Optimize ConfigMgr architecture, design, and deployment plans to reflect your environment Smoothly install ConfigMgr Current Branch and migrate from Configuration Manager 2012 Save time and improve efficiency by automating system management Use the console to centralize control over infrastructure, software, users, and devices Discover and manage clients running Windows, macOS, Linux, and UNIX Define, monitor, enforce, remediate, and report on all aspects of configuration compliance Deliver the right software to the right people with ConfigMgr applications and deployment types Reliably manage patches and updates, including Office 365 client updates Integrate Intune to manage on-premise and mobile devices through a single console Secure access to corporate resources from mobile devices Manage Microsoft's enterprise antimalware platform with System Center Endpoint Protection Using this guide's proven techniques and comprehensive reference information, you can maximize the value of ConfigMgr in your environment-no matter how complex it is or how quickly it's changing.